Filsafat Islam Dan Falsafah Sunda: Harmonisasi Teologi, Budaya, Dan Nilai-Nilai Pendidikan Agama Islam - Vikryan, Zaka; Zahra Fauziah, Alfiatu (Al-Mau’izhoh: Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine the harmonization of Islamic philosophy and Sundanese philosophy in the context of theology, culture, and the values of Islamic religious education. This study is motivated by the lack of research that synthesizes the two philosophical systems, even though both have great potential as the foundation of moderate, humanistic, and contextual Islamic religious education for the Sundanese people. This study aims to identify key concepts in Islamic philosophy and Sundanese philosophy that are relevant to Islamic religious education; analyze the intersection of the two within the framework of harmonization of theology and culture, and the values of Islamic religious education; and formulate the philosophical and pedagogical implications of this integration. This study uses a qualitative research method with a library study design combined with philosophical-hermeneutical analysis. The results show that the harmonization of the two philosophical systems produces a complementary ontological, epistemological, and axiological framework. This integration is not additive, but rather an interconnected process that combines the universality of Islamic teachings with the uniqueness of Sundanese culture. The research findings confirm that these values provide a strong conceptual foundation for the development of Islamic Religious Education (PAI) based on local wisdom, particularly in character formation, strengthening religious moderation, and internalizing ethical values in students' lives. Thus, harmonizing Islamic philosophy and Sundanese philosophy can be a relevant pedagogical strategy to address the educational needs of the Sundanese community.